Analysis of the Implementation of Policy and Integrated Transportation of Bus Rapid Transit (BRT) in Medan City - Deni Turio; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to describe the Analysis of the Implementation of Policy and Integrated Transportation of Bus Rapid Transit (BRT) in Medan City. The qualitative research method is also known as a method where the research is conducted under natural conditions. This research method is a scientific procedure or approach to obtain data with specific objectives. Data analysis is the process of systematically searching for and organizing data. The data collection techniques used in this study are observation, interviews, and documentation studies. The data obtained are then analysed through three stages: data reduction, data presentation, and verification. The results of the study show that the Medan City Government is currently implementing significant development in urban mobility with two main activities: the development of Bus Rapid Transit (BRT) and the development of Kesawan and Merdeka Square areas. Both activities emphasize the importance of developing pedestrian and cyclist facilities while facilitating the people of Medan City in accessing public transportation. These efforts are positive actions taken by the Medan City Government toward the development of sustainable urban mobility while ensuring that all corners of Medan City can be reached by quality public transportation.